Challenges for Teacher Profession in Contemporary Indonesia: A Regulatory Analysis - Saru Arifin (Lentera Hukum, 2020)
The Indonesian government shows the commitment to include teachers as a noble profession by enacting the Act on Teacher and Lecturer in 2014. This Act outlines and protects the teaching profession so that teachers are expected to be able to work safely and comfortably in carrying out their professional duties. However, the way to strengthen this teacher profession does not respond to many cases resulting in teacher insecurity and discomfort in carrying out the profession. Teachers often experience various considerable threats of violence and intimidation from students, parents, and community members. This paper will discuss the legal protection for teachers in carrying out their profession. The discussion includes the factors that often cause teachers to face criminal limits and strengthen legal protection for teachers in carrying out their noble profession. KEYWORDS: Legal Protection, Education, Teacher Profession.